Investigating Processes of Internalisation of Values Through Theatre for Development - Telisa Courtney; John Battye (Journal of Social and Political Psychology, 2018)
Used in many communities, Theatre for Development (TfD) allows performers and audiences to interrogate their cultural history and their society to promote positive social change. While many scholars have investigated the impact of TfD on audiences, very little research has investigated the psychological impact on the performers. This study attempts to fill this research gap by interviewing participants in a theatre creation project about their views on contentious social issues before, during, and after the creation of scenes involving such themes. We hypothesized that, by performing counterattitudinal and/or unfamiliar behaviours, cognitive dissonance should arise in the performers, which should result in some level of internalisation and attitude change. Results support the hypothesis, particularly in regard to the themes of ethnicity and gender (in)equality, and point to the value of using TfD processes in divided communities. This has implications for many fields, including international development, gender studies, education, and clinical psychology.